Memory skills in business - Burley-Allen, Madelyn (Crisp Pub. Menlo ParkUS, 1988)
Defines memory. Describes memory systems/ techniques as well as items which contribute to memory. These include: association, classification, and linking. Provides techniques for remembering names and numbers, as well as general principles of, and rules for memory improvement.